2022
DOI: 10.1016/j.compbiomed.2021.105176
|View full text |Cite
|
Sign up to set email alerts
|

ICU admission and mortality classifiers for COVID-19 patients based on subgroups of dynamically associated profiles across multiple timepoints

Abstract: The coronavirus disease 2019 (COVID-19) which is caused by severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) is consistently causing profound wounds in the global healthcare system due to its increased transmissibility. Currently, there is an urgent unmet need to identify the underlying dynamic associations among COVID-19 patients and distinguish patient subgroups with common clinical profiles towards the development of robust classifiers for ICU admission and mortality. To address this need, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…A study conducted in Italy in 2020 identified that, among patients who had recovered from the acute phase of the disease, 87.4% reported the persistence of at least one symptom, the most prevalent being fatigue, followed by shortness of breath 3 . These were also the two main complaints identified in another study conducted in the United Kingdom in the same year 4 . Several factors are associated with the persistence of these manifestations, such as persistent chronic inflammation, organic changes related to the disease, prolonged hospitalization, and associated intensive care 3 , 5 .…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…A study conducted in Italy in 2020 identified that, among patients who had recovered from the acute phase of the disease, 87.4% reported the persistence of at least one symptom, the most prevalent being fatigue, followed by shortness of breath 3 . These were also the two main complaints identified in another study conducted in the United Kingdom in the same year 4 . Several factors are associated with the persistence of these manifestations, such as persistent chronic inflammation, organic changes related to the disease, prolonged hospitalization, and associated intensive care 3 , 5 .…”
Section: Introductionmentioning
confidence: 66%
“…Typically, advanced age is linked with higher mortality rates and a greater need for critical care. Our sample, however, comprised of younger patients, prompting further investigation into unanalyzed factors like inflammatory markers or specific laboratory parameters that may account for these differences 4 .…”
Section: Discussionmentioning
confidence: 99%